Fischereibiologische Untersuchungen im westlichen Barentsmeer und bei Spitzbergen - Reinsch, H.H. (1981)
Johann Heinrich von Thunen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung – Information on Fishery research in 2010